Foreign Direct Investment, Indeks Kemudahan Berusaha, Dan Tarif Pajak Penghasilan Negara-Negara ASEAN - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2021)
The inflow of Foreign Direct Investment is needed by all countries in the world tobe used as a catalyst to achieve the goals of sustainable development in allaspects of a country's life. Countries in the Southeast Asia Region that aremembers of ASEAN also need Foreign Direct Investment. The success of acountry in attracting Foreign Direct Investment inflows is determined by manyfactors, including the ease of doing business and the income tax rate. In thisstudy, a comparative study was conducted between the success of ASEANcountries in obtaining Foreign Direct Investment inflows with the success ofachieving a high index of ease of doing business and the use of competitiveincome tax rates. The comparison was only made between 10 ASEAN membercountries from 11 ASEAN member countries, because of the difficulty in collecting data from 1 other ASEAN member country, namely Timor Leste. The results showed that Singapore succeeded in attracting the largest Foreign DirectInvestment inflows among other ASEAN countries, amounting to 59.10% of thetotal Foreign Direct Investment inflows from ASEAN countries. Singapore'ssuccess in attracting the largest Foreign Direct Investment inflow among otherASEAN countries is directly proportional to its achievement in obtaining the bestease of doing business index and the lowest income tax rate compared to otherASEAN countries. Meanwhile, for other ASEAN countries, there is no visiblecomparison between the success of obtaining Foreign Direct Investment with theease of doing business index and the Income Tax rate.